Bartonella henselae endocarditis in Laos - 'The unsought will go undetected' - Rattanavong, S; Fournier, P; Chu, V; Frichitthavong, K; Kesone, P; Mayxay, M; Mirabel, M; Newton, P (Public Library of Science, 2014)
Background Both endocarditis and Bartonella infections are neglected public health problems, especially in rural Asia. Bartonella endocarditis has been described from wealthier countries in Asia, Japan, Korea, Thailand and India but there are no reports from poorer countries, such as the Lao PDR (Laos), probably because people have neglected to look. Methodology/Principal Findings We conducted a retrospective (2006–2012), and subsequent prospective study (2012–2013), at Mahosot Hospital, Vientiane, Laos, through liaison between the microbiology laboratory and the wards. Patients aged >1 year admitted with definite or possible endocarditis according to modified Duke criteria were included. In view of the strong suspicion of infective endocarditis, acute and convalescent sera from 30 patients with culture negative endocarditis were tested for antibodies to Brucella melitensis, Mycoplasma pneumoniae, Bartonella quintana, B. henselae, Coxiella burnetii and Legionella pneumophila. Western blot analysis using Bartonella species antigens enabled us to describe the first two Lao patients with known Bartonella henselae endocarditis. Conclusions/Significance We argue that it is likely that Bartonella endocarditis is neglected and more widespread than appreciated, as there are few laboratories in Asia able to make the diagnosis. Considering the high prevalence of rheumatic heart disease in Asia, there is remarkably little evidence on the bacterial etiology of endocarditis. Most evidence is derived from wealthy countries and investigation of the aetiology and optimal management of endocarditis in low income countries has been neglected. Interest in Bartonella as neglected pathogens is emerging, and improved methods for the rapid diagnosis of Bartonella endocarditis are needed, as it is likely that proven Bartonella endocarditis can be treated with simpler and less expensive regimens than “conventional” endocarditis and multicenter trials to optimize treatment are required. More understanding is needed on the risk factors for Bartonella endocarditis and the importance of vectors and vector control.